Accelerators and Decelerators of Scaleup Growth: Key Factors and Circumstances for Sustainable Expansion - Slávik, Štefan; Mišúnová Hudáková, Ivana; Bednár, Richard; Hajduová, Zuzana (European Journal of Sustainable Development, 2024)
Scaleup is the development phase of a start-up that has solved its initial problems and is facing the challenge of achieving significant business rise and growth. However, it is still a small company whose growth is not easy. The goal of the research is to deepen and expand knowledge about the circumstances and factors that accelerate and/or slow down its growth. The source of new knowledge is field research on a sample of 97 scaleups. Researchers have personal experience from guided interviews with scaleup founders, which they recorded in the questionnaire. Respondents' statements were analyzed using critical discourse analysis (CDA) with the support of artificial intelligence. The result of the research is the identification of external growth accelerators, external growth decelerators, internal growth accelerators, and internal growth decelerators of scaleups. Each group of factors influencing growth contains five factors, the order of which corresponds to the weight of their positive or negative impact on growth. In addition, other accompanying circumstances affecting growth were similarly identified. The acquired knowledge can be used to evaluate the growth possibilities of a particular scaleup and to implement corrective measures according to the external and internal possibilities of the company. The research revealed an original and complex structure of factors and circumstances that influence the growth of scaleups and thus contribute to improving strategic thinking in this type of enterprise. Keywords: scaleup, accompanying circumstances of growth, external and internal growth accelerators, external and internal growth decelerators.